2004
DOI: 10.1210/me.2003-0222
|View full text |Cite
|
Sign up to set email alerts
|

Hoxa11 Regulates Stromal Cell Death and Proliferation during Neonatal Uterine Development

Abstract: Increasing evidence indicates that the Hoxa11 gene plays a critical role in the proper development of the uterus. In this report, we describe potential altered cellular processes in the developing uterus of Hoxa11 mutants. Histologic analysis demonstrates normal uterine morphology in Hoxa11 mutants as compared with controls at the newborn stage and d 7 after birth. Stromal tissue was moderately reduced in the Hoxa11 mutant uterus by d 14 after birth and was absent by d 21 after birth. There is decreased cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…The primary argument against proteinmediated evolution of gene regulatory networks is the negative pleiotropic effects of mutations that are ascribed to changes in protein-coding genes (3,4). For example, given the multiple functions of HoxA-11 in blood cell differentiation (43) and development of the body axis (44), limbs (25,45), kidney (46,47), and male (27,28) and female reproductive systems (25,27,28), it seems unlikely that a novel function could emerge in endometrial cells without simultaneously having deleterious effects in these other contexts. However, our data indicate that selection acted to maintain ancestral functions during the emergence of a novel function by recruiting amino acid sites that were previously under weak functional constraints and thus free to acquire novel functions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary argument against proteinmediated evolution of gene regulatory networks is the negative pleiotropic effects of mutations that are ascribed to changes in protein-coding genes (3,4). For example, given the multiple functions of HoxA-11 in blood cell differentiation (43) and development of the body axis (44), limbs (25,45), kidney (46,47), and male (27,28) and female reproductive systems (25,27,28), it seems unlikely that a novel function could emerge in endometrial cells without simultaneously having deleterious effects in these other contexts. However, our data indicate that selection acted to maintain ancestral functions during the emergence of a novel function by recruiting amino acid sites that were previously under weak functional constraints and thus free to acquire novel functions.…”
Section: Resultsmentioning
confidence: 99%
“…The Abd-B-related Hox gene HoxA-11 is required is to activate expression of PRL (V.J.L., B.G., and G.P.W., unpublished data). In addition to its role in PRL regulation, HoxA-11 is essential for the pre-and postnatal development of the female reproductive tract and is required for successful implantation of the mammalian blastocyst (25)(26)(27)(28). Remarkably, a previous molecular evolutionary analysis of HoxA-11 suggested that an episode of positive Darwinian selection occurred in the stem-lineage of placental mammals, coincident with the origin of the uterus and pregnancy (29).…”
mentioning
confidence: 99%
“…Abnormalities in the development of mullerian structures were observed in mice with Hox gene mutations [17]. Hoxa11 mutant female mice display normal uteri at birth, but decreased cellular proliferation/increased apoptosis result in the absence of stromal tissue by day 21 after birth [18]. Hoxa11 mutant mice were sterile, likely due to reduced stromal tissue and endometrial gland development in the uteri [19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…HoxA-10 appears to be required for successful uterine implantation (Benson et al 1996;Lim et al 1999). Knock-outs of and mutations in HoxA-11 demonstrate that this gene is critical for female reproductive tract endometrium development, both before and after birth (Gendron et al 1997;Wong et al 2004). Other reproductive tract defects in both males and females are also seen in HoxA-11 mutants ( Hsieh- Li et al 1995).…”
Section: A Conserved System Of Mammalian Developmentmentioning
confidence: 99%